2021
DOI: 10.21203/rs.3.rs-609240/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence supporting deployment of next generation insecticide treated nets in Burkina Faso: bioassays with either chlorfenapyr or piperonyl butoxide increase mortality of pyrethroid-resistant Anopheles gambiae s.l.

Abstract: Background Pyrethroid resistance poses a major threat to the efficacy of insecticide treated nets (ITNs) in Burkina Faso and throughout sub-Saharan Africa, particularly when resistance is present at high intensity. For such areas there are alternative ITNs available, including the synergist piperonyl butoxide (PBO)-based ITNs and dual active ingredient ITNs such as Interceptor G2 (treated with chlorfenapyr and alpha-cypermethrin). Before deploying alternative ITNs on a large scale it is crucial to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…populations to DDT and PY observed in the four ricegrowing sites is correlated with the frequency of the Kdr mutation, implying that the Kdr mutation is the major mechanism of crossresistance to these two classes of insecticides (organochlorines and PYs) in An. gambiae, as suggested by many other studies 25,26 . Furthermore, the work of Nanmoutougou et al in Burkina-Faso showed that in An.…”
Section: Discussionsupporting
confidence: 69%
“…populations to DDT and PY observed in the four ricegrowing sites is correlated with the frequency of the Kdr mutation, implying that the Kdr mutation is the major mechanism of crossresistance to these two classes of insecticides (organochlorines and PYs) in An. gambiae, as suggested by many other studies 25,26 . Furthermore, the work of Nanmoutougou et al in Burkina-Faso showed that in An.…”
Section: Discussionsupporting
confidence: 69%